(untitled) (Journal of Global Accounting, 2023)
The study examined how the implementation of various fiscal policy instruments in Anambra State affect the performance of Micro, Small and Medium Enterprises operating in Awka South Local government area. Specifically; it examined the effect of double taxation on the periodic performance of Micro, Small and Medium Enterprises (MSMEs). It further assessed the relationship between Tax based projects and the performance of Micro, Small and Medium Enterprises (MSMEs). The exploratory research design was adopted while a total of one hundred and nineteen (119) respondents were sampled from a population of one hundred and sixty eight (168) Senior staff and Personnel of Finance departments of eleven (11) selected Small and Medium Enterprises in Awka South Local Government Area of Anambra State, Nigeria using the stratified sampling technique. The primary data for this study were collated through structured questionnaire. Descriptive statistics was used for the calculation of mean, percentages and frequency distribution. The hypotheses were tested using Simple linear regression analysis and the Spearman Ranked Order Correlation test. Results obtained showed that double taxation has a significant but negative effect on the periodic performance of MSMEs in Awka south local government area of Anambra state (p-value = 0.000). It was also discovered that tax based projects has a significant and positive relationship with the performance of MSMEs in Awka south local government areas of Anambra state (p-value = 0.000). The study therefore concludes that multiple taxation can be a major barrier to business growth and sustainability, increasing the cost of doing business, reducing profitability of MSMEs, and limiting the ability of these small businesses to improve and reinvest in their scope of operations and deploy of technological innovations so as to boost expansion. As a result, it is recommended that government should review its tax policies at the State and Local governments’ level to effectively reconcile gray areas in their fiscal policies practices that readily exposes MSMEs to unhealthy and unjust double taxation. Also, government should prioritize tax-based projects that have a direct impact on MSMEs, such as the construction of roads, electricity, and water infrastructure. This would improve the overall business environment of MSMEs and promote their growth and progressive development..